Exchange Rate Regimes and Economic Performance in Africa: which Lessons to Be Drawn for WAEMU Countries? - Sall, Abdoul Khadry (DEMO, 2017)
The objective of this paper is to evaluate the influence of the exchange rate regime on macroeconomic performance in order to draw lessons for WAEMU countries where fixed exchange policy characterizes the monetary regime. For this, a panel data estimation using the generalized method of moments (GMM) system was adopted and carried out on 32 countries to assess the impact of exchange rate regimes on macroeconomic performance during the 1980-2010 period. Th e results show that the fixed exchange regime is better than fl exible and intermediate exchange regimes to maintain low and stable inflation through discipline effect rather than credibility effect. Furthermore, growth in fixed exchange regime countries is lower than in all more flexible exchange regime countries. Specifically, these fixed exchange regime countries seem to record growth rate lower than countries in intermediate exchange regime. As for the associated flexible exchange regime coefficient is positive and significant. It reflects that countries with flexible exchange regime may have growth rate higher than countries in intermediate exchange regime. Th e implication to be drawn for WAEMU countries is that the search for a domestic nominal anchor would maintain inflation at low and stable levels while improving growth performance.(original abstract)
Keywords: Exchange rates; Inflation; Economic growth; Monetary policy; State monetary policy